Morphogenetic routes of long-term embryogenic callus culture of Areca catechu - H. C. Wang; J. T. Chen; W. C. Chang (Biologia Plantarum, 2010)
Early morphogenetic events and repetitive embryogenesis from callus culture of betel nut palm (Areca catechu L.) were studied using scanning electron microscopy. On Murashige and Skoog (MS) medium supplemented with 2 mg dm-3 dicamba, callus culture has capacity to form plantlets via somatic embryogenesis and to form secondary embryos for about 4 years. However, various abnormal embryos without differentiation of the leaf sheath and shoot apical meristem were observed, which showed bell-shaped and then cup-shaped or mushroom-shaped structures. These abnormal embryos contained distinctive structures, including a disk-shape interior region, surfaces with grooves and a stalk-like posterior region. During subculture, these abnormal embryos enlarged, became deformed and gradually lose their shape and then converted into nodular, compact embryogenic callus. It was also found that secondary embryos originated from interior surfaces or posterior regions of abnormal embryos, and gave rise to the next cycle of normal and abnormal embryos.